Why Do Inpatient Visits Decrease during the Covid-19 Pandemic? A Case Study in Hospital, Malang Regency - Lukito, Anggun Agatha Cristy; Widyaningrum, Kurnia (Fakultas Kedokteran Universitas Brawijaya, 2021)
The Covid-19 pandemic has caused a decreasing number of non-Covid-19 inpatient visits in almost all hospitals, including the hospital where the study was conducted, which experienced decreasing Bed Occupancy Rate (BOR) up to 35.5%. This study aimed to identify the factors causing the decrease in the number of inpatients at the hospital. The research was conducted using a case study approach at a type D hospital in Malang Regency. Data was collected through a Focus Group Discussion (FGD) analyzed using a Fishbone Diagram combined with 5 whys and triangulation using secondary data and surveys. FGD respondents determined were eight respondents consisting of the Head of Inpatient Room, the Coordinator of Inpatient Room, the Coordinator of Outpatient, the Head of the Public Relations and Marketing Unit, and the Coordinator of the Admission Department. The results show that the causes can originate from human, method, market, and environmental aspects. Distrust in hospitals is caused by negative stigmatization and instructions to delay hospital services and communication barriers due to media as a consequence of implementing health protocols.